Role of the PI3K/Akt pathway in cadmium induced malignant transformation of normal prostate epithelial cells. - Kulkarni, Priyanka (Toxicol Appl Pharmacol, 2020)
This study investigated the role of the PI3K/Akt pathway in cadmium (Cd) induced malignant transformation of normal prostate epithelial (PWR1E and RWPE1) cells. Both PWR1E and RWPE1 cells were exposed to 10μM Cd for one year and designated as Cd-PWR1E and Cd-RWPE1. Cd-RWPE1 cells robustly formed tumors in athymic nude mice. Functionally, Cd-exposure induced tumorigenic attributes indicated by increased wound healing, migration and invasion capabilities in both cell lines. RT(2)-array analysis revealed many oncogenes including P110α, Akt, mTOR, NFKB1 and RAF were induced whereas tumor suppressor (TS) genes were attenuated in Cd-RWPE1. This was validated by individual quantitative-real-time-PCR at transcriptional and by immunoblot at translational levels. These results were consistent in Cd-PWR1E vs parental PWR1E cells. Gene Set Enrichment Analysis revealed that five prostate cancer (PCa) related pathways were enriched in Cd-exposed cells compared to their normal controls. These pathways include the KEGG- Pathways in cancer, Prostate Cancer Pathway, ERBB, Apoptosis and MAPK pathways. We selected up- and down-regulated genes randomly from the PI3K/Akt pathway array and profiled these in the TCGA/GDC prostate-adenocarcinoma (PRAD) patient cohort. An upregulation of oncogenes and downregulation of TS genes was observed in PCa compared to their normal controls. Taken together, our study reveals that the PI3K/Akt signaling is one of the main molecular pathways involved in Cd-driven transformation of normal prostate epithelial cells to malignant form. Understanding the molecular mechanisms involved in the Cd-driven malignant transformation of normal prostate cells will provide a significant insight to develop better therapeutic strategies for Cd-induced prostate cancer.